2019
DOI: 10.1136/neurintsurg-2019-014846
|View full text |Cite
|
Sign up to set email alerts
|

Association of maximal systolic blood pressure with poor outcome in patients with hyperattenuated lesions on immediate NCCT after mechanical thrombectomy

Abstract: Background and purposeThis study aimed to investigate the relationship between blood pressure (BP) management and clinical outcome in patients with hyperattenuated lesions on non-contrast CT (NCCT) immediately after mechanical thrombectomy (MT).MethodsWe retrospectively reviewed our prospectively collected cohort for consecutive patients with acute ischemic stroke (AIS) who received MT between October 2013 and July 2018. Hourly systolic BP (SBP) and diastolic BP (DBP) values were recorded for 24 hours followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For patients with successful recanalization after MT, higher BP levels during the first 24 h after MT was correlated with a higher likelihood of sICH and mortality (15). In patients with hyperdensity on immediate non-contrast CT following MT, which indicates risk of hyperperfusion injury, BP levels during the first 24 h were linearly correlated with PH (11). In the present study, we found that SBP mean and SBP max at the time of successful recanalization after MT with general anesthesia were associated with a higher risk of PH-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with successful recanalization after MT, higher BP levels during the first 24 h after MT was correlated with a higher likelihood of sICH and mortality (15). In patients with hyperdensity on immediate non-contrast CT following MT, which indicates risk of hyperperfusion injury, BP levels during the first 24 h were linearly correlated with PH (11). In the present study, we found that SBP mean and SBP max at the time of successful recanalization after MT with general anesthesia were associated with a higher risk of PH-2.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations of the American Heart Association/American Stroke Association guidelines for BP control in LVO patients treated with MT indicate that an optimal BP target that simultaneously avoids the risk of hemorrhagic transformation and impairment of cerebral perfusion remains unknown (4). Avoiding hypoperfusion injury in ischemic tissue and hyperperfusion injury in reperfused tissue are both essential for BP management after MT (11), indicating that the BP target following MT should not be too high or too low. Several previous studies had demonstrated a U-shaped relationship between admission SBP and mortality in AIS patients (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial using murine models demonstrated the favorable effect of BP lowering after recanalization, 69 while a post hoc analysis of the SIESTA trial found no correlation between BP lowering and short-or long-term functional outcomes. 70 Moreover, in line with some retrospective studies that found that hypertension is associated with worse outcomes, [71][72][73][74][75] elevated BP after MT may need to be lowered. All of these studies are not BP-based interventional studies; RCTs are needed, and more attention should be paid to several aspects as follows when exploring the influence of BP on patient outcomes after MT (Figure 1).…”
Section: Influence Of Bp On Outcomesmentioning
confidence: 72%
“…85 Goyal et al found that BP <160/90 mmHg within 24 h after MT resulted in less mortality, 71 while Ding et al indicated that SBP≤140 mmHg was related to better outcomes and lower parenchymal hemorrhage. 75 Matusevicius et al reported that 100≤SBP≤119 mmHg contributed to better functional outcomes in patients with successful recanalization, and the range was 120-139 mmHg in patients with unsuccessful recanalization. 78 Maier et al found that a maximum SBP of 159 mmHg was the best cutoff for patients with successful recanalization, while a higher SBP was associated with poor functional outcomes.…”
Section: Thresholdmentioning
confidence: 99%
“…This area of hyperatenuation is more prone to hemorrhagic transformation after effective recanalization. In a retrospective study of a prospectively collected cohort of the consecutive acute ischemic stroke patients due to large vessel occlusion that underwent to a successful mechanical thrombectomy, 50% of the subjects exhibited areas of the hyperatenuation in the post-procedure non contrast CT [18]. In this particular group, the probability of symptomatic hemorrhagic transformation (parenchymal hematoma) due to reperfusion injury increased with each increment of the post-operative maximum systolic blood pressure in the first 24 h. Until further evidence from randomized clinical trials are available, it appears prudent to try to correct the persistence of an acute hypertensive response after a successful mechanical thrombectomy to avoid hemorrhagic reperfusion injury.…”
Section: Management Of the Blood Pressure In Acute Ischemic Stroke Immediately After Successful Endovascular Recanalizationmentioning
confidence: 99%